A systematic literature review on the forest health biomonitoring technique: A decade of practice, progress, and challenge - Abas, Azlan (Frontiers in Environmental Science, 2023)
The approach for monitoring forest health has evolved in tandem with the advancement of new technology. The application of biomonitoring techniques, on the other hand, has been positive and has made its own contribution to forest management. Many studies have been conducted in the last decade which use the biomonitoring techniques in assessing the forest health status. Therefore, this study aims to systematically review the forest health biomonitoring techniques in the last decade. This study used the PRISMA guidelines as the protocol to search and analyze all the papers. This study selected 72 papers for a thematic analysis which eventually identified four main biomonitoring techniques, namely: a) diversity distribution, b) morphological observations, c) trace elements, minerals and physiological measurements, and d) behavioral observations. The biomonitoring techniques applied to monitor forest health has evolved with numerous ways that can support existing technologies, as well as help educate people on the necessity of protecting and safeguarding the natural forest environment.